Properties of cereal brans: a review - Chinma, Chiemela Enyinnaya; Ramakrishnan, Yogeshini; Ilowefah, Muna; Mat Gani, Hanis Syazwani; Syed Muhammad, Sharifah Kharidah (AACC International, 2015)
Cereal brans are functional ingredients with high nutritive value and enormous health properties. Cereal brans have not been fully utilized in food systems despite their health benefits. This review presents an overview on the physical, chemical, microbiological, functional, and sensory properties of cereal brans for possible comparisons and selection to enhance the utilization of this underutilized milling fraction.